2022
DOI: 10.3390/medicina59010012
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Replacement vs. Surgical Aortic Valve Replacement for Long-Term Mortality Due to Stroke and Myocardial Infarction: A Meta-Analysis during the COVID-19 Pandemic

Abstract: Background and objectives: One of the leading causes of mortality and morbidity in people over the age of 50 is stroke. The acceptance of transcatheter aortic valve replacement (TAVR) as a treatment option for severe symptomatic aortic stenosis (AS) has increased as a result of numerous randomized clinical trials comparing surgical aortic valve replacement (SAVR) and TAVR in high- and intermediate-risk patients, showing comparable clinical outcomes and valve hemodynamics. Materials and Methods: An electronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Twenty-four studies out of the thirty-three selected evaluated the risk of stroke. Sixteen studies [ 6 , 8 , 11 , 13 – 16 , 22 , 24 , 26 – 29 , 34 , 36 – 38 ] found the hazard for stroke to be similar between TAVI and SAVR. Two studies [ 9 , 18 ] found TAVI to have a higher rate of stroke than SAVR, with the first study considering only high-risk surgical patients and the second one including patients with all risk classes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four studies out of the thirty-three selected evaluated the risk of stroke. Sixteen studies [ 6 , 8 , 11 , 13 – 16 , 22 , 24 , 26 – 29 , 34 , 36 – 38 ] found the hazard for stroke to be similar between TAVI and SAVR. Two studies [ 9 , 18 ] found TAVI to have a higher rate of stroke than SAVR, with the first study considering only high-risk surgical patients and the second one including patients with all risk classes.…”
Section: Resultsmentioning
confidence: 99%
“…Four [18,24,27,35] studies found cardiac mortality to be similar between TAVI and SAVR. Two studies [29,36] favored SAVR over TAVI and one [30] reported a lower rate for TAVI in the first year and similar rates in the second year of follow-up. One study [34] reported similar rates in the first year of follow-up, higher rates in the second year for TAVI, and similar rates until year five of follow-up.…”
Section: All-cause Mortalitymentioning
confidence: 99%